The Effect of Animated Educational Videos on Adolescents' Knowledge of Reproductive Health in Efforts to Prevent Stunting - Intan Lestari; Agrina Agrina; Febriana Sabrian (Journal of Education Technology Information Social Sciences and Health, 2025)
Stunting is a growth disorder in children caused by inadequate nutrition, affecting their physical and cognitive abilities. One contributing factor to stunting is early marriage, which is closely related to a low understanding of adolescent reproductive health. This study aims to analyze the effect of animated educational video media on adolescents' knowledge of reproductive health in efforts to prevent stunting. This quantitative study uses a pre-experimental design with a one-group pre-test and post-test arrangement. Data collection uses total sampling with 66 respondents. The research is conducted at SMPN 5 Satap Kunto Darussalam. The measurement tool is a validated and reliable questionnaire on reproductive health, sexuality, and teenage pregnancy prevention. The data is analyzed using the Wilcoxon test. The results show an increase in adolescents' knowledge before and after the intervention with animated educational video media. Statistical tests confirm that the intervention is effective in improving adolescents' average knowledge regarding reproductive health, with a p-value of 0.000 (< α 0.05). Animated educational video media effectively improves adolescents' knowledge about reproductive health in efforts to prevent stunting. This media can serve as a useful tool for adolescents to enhance knowledge and actions related to reproductive health and stunting prevention.